Response to phenological manipulation through planting time for productivity of banana (Musa AAA, Grand Naine) under subtropics - KUMAR, DINESH; RAJAN, S; SRIVASTAVA, K K (The Indian Journal of Agricultural Sciences, 2021)
The present study was carried out to standardize the ideal planting time in response to phenological changes inbanana (Musa AAA, Grand Naine) for better yield and quality under subtropical conditions during 2017-19 at firstblock of ICAR-CISH, Rehmankhera, Lucknow. The tissue cultured banana cv. Grand Naine were planted at monthlyintervals w.e.f 15 June 2017 to 15 May 2018 in the experimental field at 1.8 m × 1.5 m spacing. The banana plantedduring 15th June and 15 July had the highest pseudostem circumference, leaf area, leaf area index and fruit yield,respectively. Pseudostem height and leaf number were highest in banana planted during 15 November. The GrowingDegree Days (GDD) from planting to shooting were calculated and found to be optimum and duration from plantingto shooting was also minimum when planted during 15 June and 15 July. There were no leaf emergence during wintermonth especially December, January and February due to low temperature irrespective of planting dates in bananaunder subtropics. Quality parameters such as bunch weight, number of hands, total fingers, and weight and numberof fingers in 2nd hand were recorded in banana planted on 15 of July. The TSS content was higher when planted on15 June and acidity when planted on 15 October. The ideal time for planting of banana in present study was 15 Juneand 15 July for better yield and quality under subtropical conditions.